Experimental investigation on flow pattern and void fraction for two-phase gas-liquid upflow in a vertical helically coiled micro-channel - Sira Saisorn; Phakkhanan Benjawun; Adirek Suriyawong; Somchai Wongwises (International Journal of Thermofluids)
To contribute toward state-of-the-art microfluidic technology, our experiments were conducted to study gas-liquid adiabatic upflow phenomena in a helical micro-channel having a channel diameter of 0.87 mm, a coil diameter of 50 mm, and a helical pitch of 20 mm. The presence of centrifugal acceleration in the micro-scale flow is given as follows. The unique flow pattern having the throat-like gas-core flow generally detected in the straight micro-tube was still present in the curved test section. The void fraction characteristics were not able to match with the homogeneous flow model. The slip ratio data explicitly showed that the annular flow tended to be highly affected by the secondary flow when compared to the throat-annular flow. The prediction based on different approaches indicated that the data aligned well with drift flux model incorporating inertia and channel orientation effects.